(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
Information hiding is one of multimedia security tasks need to develop and update in Continuously. Thus, the researchers work in this field and interest in developing and improving the information hiding techniques. In this paper, a new method for develop least significant bits (LSB) method is introduced. The method includes a schema for hiding two bits of secret text in each pixel (least and penultimate bits of pixel) in gray image considering motif Z, U, N, and C patterns. The method is implemented on different standard images with size 512*512 and hide different secret text lengths. The experimental and results show the efficiency of method that hide two bits in each pixel compare with the traditional LSB method that hide one bit of data in each pixel of image. The results show that the proposed method produces a good accuracy of stego image near to the original LSB method in terms of PSNR accuracy metric.